2007
DOI: 10.1021/la702352x
|View full text |Cite
|
Sign up to set email alerts
|

Single-Molecule Measurement of the Strength of a Siloxane Bond

Abstract: Increasing the mechanical stability of artificial polymer materials is an important task in materials science, and for this a profound knowledge of the critical mechanoelastic properties of its constituents is vital. Here, we use AFM-based single-molecule force spectroscopy measurements to characterize the rupture of a single silicon-oxygen bond in the backbone of polydimethylsiloxane as well as the force-extension behavior of this polymer. PDMS is not only a polymer used in a large variety of products but als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
68
0
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(77 citation statements)
references
References 39 publications
5
68
0
3
Order By: Relevance
“…8,50,75 The latter strategy was used in a careful study of mechanical properties of polydialkylsiloxanes, which demonstrated the lack of a correlation between the estimated barrier lowering of the Si-O bond dissociation and the strain energy (either total or per Si-O bond) and the absence of a unique fit of the experimental data to standard models of force-dependent kinetics. 41 The latter findings are consistent with calculations presented in Section 2a (Fig. 11A).…”
Section: Molecular Interpretation Of Smf Experimentssupporting
confidence: 92%
See 2 more Smart Citations
“…8,50,75 The latter strategy was used in a careful study of mechanical properties of polydialkylsiloxanes, which demonstrated the lack of a correlation between the estimated barrier lowering of the Si-O bond dissociation and the strain energy (either total or per Si-O bond) and the absence of a unique fit of the experimental data to standard models of force-dependent kinetics. 41 The latter findings are consistent with calculations presented in Section 2a (Fig. 11A).…”
Section: Molecular Interpretation Of Smf Experimentssupporting
confidence: 92%
“…In practice, rapid detachments are observed at forces of a few nN. 8,41 In a less common configuration, a macromolecule is stretched rapidly to a desired restoring force and maintained at such a force until it ruptures. 50 This approach is best suited to a bimolecular reaction, whose rates can be controlled by the concentration of a reagent in solution.…”
Section: Measurements Of Force-dependent Kinetics In Stretched Polymersmentioning
confidence: 99%
See 1 more Smart Citation
“…An ideal molecule where the cis state had an elasticity as high as the trans state could reach 100 % efficiency if it could hold and switch against forces of 8 nN, but such a force cannot be reached as covalent bonds already break at few nN forces. [61,62] How does this compare to biological molecular motors? The efficiency of the bacteriophage f29 is more than 50 % and this at low forces compared to the synthetic molecular motor.…”
Section: Discussionmentioning
confidence: 99%
“…Both experimental and theoretical investigations suggest the pulling force necessary to break a chemical bond be a few nanonewtons1, 37-39 while rupturing structures maintained by non-covalent bonds, such as unfolding of proteins, overcoming protein-ligand interactions and unraveling a single base-pair in double-stranded DNAs, requires forces at least one order of magnitude smaller 40-43. A few reports37, 38 have been published on bonding the molecule covalently at both ends before the pulling experiments, while in the majority of experiments, the molecule is picked up randomly through non-specific interactions. Consequently, the adhesion between the AFM tip and the molecule, or between the molecule and the substrate surface, is weak compared with the force required to break a chemical bond, but probably comparable to the hydrogen bonds and hydrophobic interactions maintaining the secondary and tertiary structure of a protein (without disulfide bonds).…”
mentioning
confidence: 99%